Cấu trúc vốn và hiệu quả hoạt động của doanh nghiệp: Vai trò của cạnh tranh ngành - Châu Văn Thưởng; Trần Lê Khang; Nguyễn Công Thành (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
The research examines the influence of industry competition and the effect of capital structure on firm performance. The data includes financial statements of listed companies on Ho Chi Minh Stock Exchange (HOSE) from 2007 to 2015 in a range of 13 different industries. By applying two-step GMM technique with tangibility and non-debt tax shield employed as instrument variables for unbalanced panel data, the results indicate that capital structure has a positive impact on firm performance and that this effect becomes stronger in the markets with high levels of competition. Furthermore, these findings provide significant implications for investment and policy making among enterprises.
Keywords: Industry competition; Capital structure; Firm performance